THE EFFECT OF DISCOUNTS AND SCARCITY MESSAGES ON IMPULSE BUYING IN SKINTIFIC CONSUMERS THROUGH LIVE SHOPEE (CASE STUDY OF FEB STUDENTS OF BANDAR LAMPUNG UNIVERSITY) - Erika Lucas; Ardansyah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Shopee is a corporation in the field of electronic shopping. One of the beauty brands that attracts attention from Shopee users is Skintific. Skintific often holds flash sales in the form of discounts or discounts when live Shopee. This is what causes impulsiveness in buyers. This research aims to find out the impact of discounts and scarcity messages on impulse buying on Skintific consumers through live Shopee. This research uses associative research type, applying quantitative descriptive methods. The sample used in this research was 100 students of the Faculty of Economics and Business, Bandar Lampung University. The data in this study was taken using questionnaires. The research data that has been collected is then analyzed by applying multiple linear regression using the SPSS for windows application. Research findings show that rebates partially affect impulse buying. Research findings also show that scarcity messages partially affect impulse buying. While rebates and scarcity messages affect impulse buying simultaneously.